Dynamic analysis of subway station subjected to internal blast loading - He, Wei; Chen, Jian-yun; Guo, Jing (Journal of Central South University, 2011)
The study was motivated by the fact that explosion inside the subway structure may not only cause direct life loss, but also damage the subway structure and lead to further loss of lives and properties. The propagation law of explosion wave in the subway station was analyzed and a simplified model of overpressure in the subway station was also proposed. Whereafter, the improved dynamic cam-clay model of soil and the concrete damaged plasticity constitutive model were used for the dynamic analysis of the subway station. Meanwhile, the influences of soil stiffness and burial depth on the dynamic response of the subway station were looked into. The results show that the multi-peak overpressure in the subway station does not appear, and large stresses concentrate on the central column and the floor slab of the subway station, so some special reinforcement measures should be taken in these parts. The effect of soil stiffness and burial depth on the stress of the central column is little; however, the effect on the stress of the station side wall is relatively obvious.